CO2 emissions response to GDP and crude oil price shocks: Evidence from India and China using SVAR Model - Matali Mahajan; Dr. Ash Narayan Sah (Sustainable Futures)
Global CO₂ emissions and warming remain critical challenges worldwide, with emission reduction central to attaining the UN Sustainable Development Goals. This paper investigates the relationship between WTI prices, Inflation, CO2 emission, and GDP in India and China. Based on annual data spanning 1980–2019 for India and 1990–2019 for China, sourced from the “World Bank and Our World in Data” database, we investigate these interactions via a Structural Vector Autoregression framework, using impulse response functions and forecast error variance decomposition to map the effects. Our empirical analysis reveals positive links between WTI and Inflation in the long run, aligned with cost-push inflation concepts. A single innovative fluctuation in GDP increases CO₂ emissions, corroborating the Environmental Kuznets Curve's tenet. Our results indicate that neither country has reached peak CO₂ levels, suggesting continued challenges in balancing economic growth with sustainability goals. These insights highlight the need for policies that address short-term oil price volatility and support sustainable development.